Kinesthetic imagery of musical performance - Lotze, Martin (Frontiers in Human Neuroscience, 2013)
Musicians use different kinds of imagery. This review focuses on kinesthetic imagery, which has been shown to be an effective complement to actively playing an instrument. However, experience in actual movement performance seems to be a requirement for a recruitment of those brain areas representing movement ideation during imagery. An internal model of movement performance might be more differentiated when training has been more intense or simply performed more often. Therefore, with respect to kinesthetic imagery, these strategies are predominantly found in professional musicians. There are a few possible reasons as to why kinesthetic imagery is used in addition to active training; one example is the need for mental rehearsal of the technically most difficult passages. Training difficult passages repeatedly has the potential to induce fatigue in tendons and muscles and can ultimately result in the development of dystonia. Another reason for mental practice is that mental rehearsal of the piece helps to improve performance if the instrument is not available for actual training as is the case for professional musicians when they are travelling to various appearances. Overall, mental imagery in musicians is not necessarily specific to motor, somatosensory, auditory or visual aspects of imagery, but integrates them all. In particular, the audiomotor loop is highly important, since auditory aspects are crucial for guiding motor performance. Furthermore, slight co-movement, for instance of the fingers, usually occurs when imagining musical performance, a situation different to the laboratory condition where movement execution is strictly controlled. All these aspects result in a distinctive representation map for the mental imagery of musical performance. This review summarizes behavioral data, and findings from functional brain imaging studies of mental imagery of musical performance.